Pengaruh Pelatihan dan Motivasi terhadap Kinerja Karyawan pada PT. Andalan Rantai Pasok Indonesia (Arpilog) - Nadia Maulaya; Henny Armaniah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Human resource management has an important role as a driving force in the company, in improving employee performance, periodic training and motivating employees can be carried out. This study aims to determine the effect of training and motivation on employee performance at PT Andalan Rantai Pasok Indonesia. The type of research used is quantitative research. The population in this study was the entire sample size of 31 respondents. The analysis technique used in this study is the validity test method, reliability test, classical assumption test, multiple linear regression, and hypothesis testing using SPSS 26. The results showed that the Training Variable partially had a significant effect on Employee Performance with a t value of 2.244> 2.051 and a Sig value of 0.033 <0.05 and the Motivation Variable partially had a significant effect on Employee Performance with a t value of 3.137> 2.051 and a Sig value of 0.004<0.5. The F test shows that together, training and motivation have a significant effect on employee performance (F = 10,971, p = 0.000). So it can be concluded that Training and Motivation have a positive and significant effect on employee performance.